Characterization of collagen from Java barb (Barbonymus gonionotus) skin and its effect on selected properties of yogurt - Asep A. Prihanto; Happy Nursyam; Yoga D. Jatmiko; Siti Nur H. Oslan; Abdul A. Jaziri; Febriantoni; Karina D. Maudy (Hasanuddin University Food Science and Technology Study Program, 2023)
Wastes of Barbonymus gonionotus (Java barb) skin can be processed as collagen as a food additive. Yogurt is a functionaldrink that has gained attention. This study aimed to characterize yogurt added with collagen from Java barb skin. The solutions used to extract the collagen were (A) 1:10 (w/v) for 24 h, (B) 1:20 (w/v) for 24 h, (C) 1:10 (w/v) for 36 h, and (D) 1:20 (w/v) for 36 h. The obtained collagen was added to yogurt at concentrations of 1%, 2%, and 3%. The yogurt was then examined for its protein content, pH, and titratable acidity. The highest yield of collagen was obtained from treatment D, with a value of 52.54% ± 0.94%. All the extracted collagens had triple-helix structures. The presence of α1 and α2 was also confirmed by sodium dodecyl-sulfate polyacrylamide gel electrophoresis, and the amino acid patterns were found to be either Gly-Pro-Ala or Gly-Pro-Arg. The addition of collagen to yogurt at a concentration of 3% produced a significant increase in protein content (3.82%). In comparison, pH and titratable acidity did not show any significant changes. However, the titratable acidity at a collagen concentration of 3% showed a small increase of 1.14% ± 0.71% at the end of fermentation. In conclusion,collagen was successfully extracted with relatively high yields, and collagen-added yogurt met industry standards. The addition of collagen at a concentration of 3% increased the protein content of yogurt and only had a slight effect on its selected characteristics.